Islamic Philanthropy and Covid-19 Pandemic Crisis: The Socio-Economic Role of Nahdhatul Ulama - Zainal Abidin (al-Uqud : Journal of Islamic Economics, 2021)
Coronavirus has evolved into a global pandemic. The virus, which was first discovered in Wuhan in China, has quickly and massively spread throughout the world, and it has even paralyzed global socio-economic activities. In Indonesia, the Covid-19 pandemic first appeared in Jakarta. In a few days, it spread to all regions and islands, including Madura, one of East Java islands with a strict, strong religious scent and has considerable respect to religious structures and symbols, like the Islamic organization Nahdhatul Ulama' (NU). This study examined this Islamic organizations' socio-economic role in Covid-19 countermeasures through philanthropic activities. This qualitative study uses primary data and secondary data. This study describes how NU implements its socio-economic role in mitigating the spread of Covid-19 pandemic in Madura through philanthropic activities.